2016
DOI: 10.1007/978-3-319-28112-4_21
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Agricultural Land in Western Australia: A New Decision Tool for Planning

Abstract: The Department of Agriculture and Food, Western Australia, has worked closely with state and local planners and agricultural practitioners over the last 4 years to develop a new way to identify high quality agricultural land (HQAL). This methodology combines land capability or suitability for horticulture and dry land cropping and grazing with irrigation supplies, rainfall and yield information. It then ranks large tracts of "similar" land according to its versatility for a range of agricultural land uses. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Studies show that climatic parameters, topography, and soil are the most important parameters in determining suitable areas for vine cultivation 8,33,34 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that climatic parameters, topography, and soil are the most important parameters in determining suitable areas for vine cultivation 8,33,34 …”
Section: Methodsmentioning
confidence: 99%
“…Studies show that climatic parameters, topography, and soil are the most important parameters in determining suitable areas for vine cultivation. 8,33,34 It is worth mentioning that to process statistical data, SPSS 19 statistical software was used (before preparing interpolation maps). The Kolmogorov-Smirnov test was used to ensure normality, and a box plot was used to identify outliers.…”
Section: Data Preparationmentioning
confidence: 99%
“…Geographical information systems are important in various fields of life, including military, civil, engineering and agricultural, and this is what will be focused on [5]. mentioned that the functions of GIS are in collecting and entering data for the study area after it has been scanned, then processing the data by special programs by arranging and indexing it, and finally outputting the results in the form of maps, scales, and illustrations that facilitate decision-making [6], explained the elements of a geographic information system and that the strength of the system depends on the extent to which they are linked together, and these elements are the data, the analysis of this data, the programs and the people supervising the work of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Moody and Bell (2006) showed that cumulative K uptake by plants was 35% higher than the change in exchangeable K in 30 of 37 agricultural soils from south-east Queensland, and the amounts of K extracted by NaTPB were highly correlated with K uptake across all soils, indicating that NaTPB methods could quantitatively estimate the available K. These differences may reflect the highly weathered landscapes of WA and the predominance of weathered minerals in soils (McArthur 2004) used in the study by Pal, but higher K reserves in clay-rich soils from south-east Queensland. However, past research on K-crop response experiments has heavily focused on lighter textured soils in WA, like Tenosols, Chromosols and Kandosols, which occupy about 50% of agricultural soils in WA (Brennan and Bell 2013;van Gool et al 2018). Monitoring of soil K reserves is increasingly important in all soil types to ensure that soil K supply is not constraining grain yield (Ma et al 2022).…”
Section: Introductionmentioning
confidence: 99%